A new perspective of using sequential extraction: To predict the deficiency of trace elements during anaerobic digestion. (1st September 2018) - Cai, Yafan; Wang, Jungang; Zhao, Yubin; Zhao, Xiaoling; Zheng, Zehui; Wen, Boting; Cui, Zongjun; Wang, Xiaofen
Abstract: Trace elements were commonly used as additives to facilitate anaerobic digestion. However, their addition is often blind because of the complexity of reaction conditions, which has impeded their widespread application. Therefore, this study was conducted to evaluate deficiencies in trace elements during anaerobic digestion by establishing relationships between changes in trace element bioavailability (the degree to which elements are available for interaction with biological systems) and digestion performance. To accomplish this, two batch experiments were conducted. In the first, sequential extraction was used to detect changes in trace element fractions and then to evaluate trace element bioavailability in the whole digestion cycle. In the second batch experiment, trace elements (Co, Fe, Cu, Zn, Mn, Mo and Se) were added to the reaction system at three concentrations (low, medium and high) and their effects were monitored. The results showed that sequential extraction was a suitable method for assessment of the bioavailability of trace elements (appropriate coefficient of variation and recovery rate). The results revealed that Se had the highest (44.2%–70.9%) bioavailability, while Fe had the lowest (1.7%–3.0%). A lack of trace elements was not directly related to their absolute bioavailability, but was instead associated with changes in their bioavailability throughout the digestion cycle. Trace elements were insufficient when their bioavailability was steady or increased over the digestion cycle. These results indicate that changes in trace element bioavailability during the digestion cycle can be used to predict their deficiency. Graphical abstract: Image 1 Highlights: Sequential extraction was applied to anaerobic digestion of rice straw. The order of bioavailability was Fe < Co < Cu < Mo < Ni < Zn < Mn < Se. The requirement of trace elements is not direct related to absolute bioavailability. Using the bioavailability trend to predict deficiency of trace elements is feasible.